Increasing arterial compliance by laser modification of fibro-calcific plaques - Rajebahadur, S.; Velluva Rayaroth, N.; King, J. B.; Alexandrovskaya, Yu. M.; Guagliumi, G.; Glatz, A.; Johnson, J. E.; Miranda Romero, F.; Vela, D.; Vinokur, V. M.; Milner, T. E.; Sobol, E. N. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCalcium is a constituent of numerous types of atherosclerotic plaques. While various vessel modification devices have been introduced, plaque heterogeneity presents a challenge to direct therapy to specific components within the arterial wall.AimsWe introduce a novel approach for non-destructive modification of arterial fibrocalcific plaques with controlled spatial-temporal diode-laser irradiation. The laser thermomechanical approach enables the controlled formation of microstructural defects, stress relaxation, microcracking, and plaque molding. Primary objectives of this exploratory study include: (1) Determine an optimal laser dosimetry in fibro-calcific plaques in ex vivo human arteries that mitigates against non-specific thermal injury of the vessel wall; (2) Identify arterial structural modifications; and (3) Characterize changes in lumen, vessel diameter and compliance in response to laser irradiation.MethodsDiode laser radiation with a wavelength of 1,470 nm is delivered to ex-vivo human femoral artery specimens through an optical fiber inside a semi-compliant balloon containing heavy water. Laser dosimetry at the intimal surface is specified using a numerical model informed by vessel lumen diameter and beam profile measurements. Radiometric temperature increases at the outer surface of the vessel in response to laser irradiation is measured with an infrared camera. Micro-CT and IV-OCT images, recorded before and after laser irradiation, are aligned and co-registered using customized software. Micro-CT is utilized to identify changes in calcium plaques in response to laser irradiation (microcracking, voids, change in density). Changes in lumen diameter and compliance are assessed by High Frequency IV-OCT.ResultsA candidate window for laser dosimetry is determined both theoretically and experimentally in the range of 150–300 W/cm2. Micro-CT images demonstrate fractures in calcium and changes in the plaque structure at irradiation sites with an azimuthal calcium extent greater than 300°. Increases in lumen area up to 28% and compliance up to 2.4x is observed.ConclusionThis proof-of-concept study demonstrated that modulated diode laser irradiation can modify the mechanical and structural characteristics of fibrocalcific arteries and increase vessel compliance. Additional studies are required in arteries with different levels of calcification and plaque distribution to optimize laser dosimetry for targeted vessel modifications.